'I Will Open a Path into the Interior (of Africa), or Perish': David Livingstone and the Mapping of Africa. (2nd January 2021) - Liebenberg, Elri
ABSTRACT: Although David Livingstone came to southern Africa in 1840 as a medical missionary, he soon succumbed to the lure of geographical discovery. Between 1849 and his death in 1873 he travelled widely in south-central Africa and managed to irreversibly change the map of this part of the continent. Although much has been written about his character, adventures and travels, little has been said about the maps he compiled and even less about how he made those maps. This article is an attempt to elucidate this rather unknown facet of his legacy by referring to the instruments, methods and techniques he used to collect his data and the high premium he put on the accuracy of his observations. Attention is also given to his life-long friendship with HM Astronomer at the Cape, Sir Thomas Maclear to whom he regularly sent his observations to be checked and his occasionally tempestuous relationship with the official cartographer of the Royal Geographical Society, John Arrowsmith.